2020
DOI: 10.1186/s12885-020-07218-0
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor mRNA levels determine the prognosis in triple-negative breast cancer patients

Abstract: Background: Anti-Androgen Receptor (AR) therapy holds promise for a subset of AR expressing triple-negative breast cancer (TNBC) patients. However, current AR assays are suboptimal in detecting the dynamic range of AR expression, contributing to its controversial role in TNBC disease prognosis. This study is aimed at evaluating the feasibility of qRT-PCR to sensitively and robustly detect AR mRNA levels for prognostication. Methods: mRNA expression profiling was performed on FFPE blocks from a retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
(63 reference statements)
1
6
0
Order By: Relevance
“…In luminal BC cells, the observation of a similar effect on AR gene expression, has led to the hypothesis that high LEP levels might potentiates the oncogenic effects of the ER by reducing AR levels and its inhibitory action on the ER. In contrast, opposite effects on AR expression could be observed in ER− or low ER expression cells, which would be consistent with the confirmed pro-tumorigenic role of both, LEP and the AR, in basal-like BC subtypes [ 74 , 103 ] ( Figure 6 ).…”
Section: Obesity Ar Signaling and Bcsupporting
confidence: 86%
See 1 more Smart Citation
“…In luminal BC cells, the observation of a similar effect on AR gene expression, has led to the hypothesis that high LEP levels might potentiates the oncogenic effects of the ER by reducing AR levels and its inhibitory action on the ER. In contrast, opposite effects on AR expression could be observed in ER− or low ER expression cells, which would be consistent with the confirmed pro-tumorigenic role of both, LEP and the AR, in basal-like BC subtypes [ 74 , 103 ] ( Figure 6 ).…”
Section: Obesity Ar Signaling and Bcsupporting
confidence: 86%
“…In contrast, 80–90% of ER+ tumors are also AR-positive (AR+) and associated with favorable prognoses (e.g., longer relapse-free survival, lower tumor grade, and smaller tumor size) [ 97 , 98 ], which has been confirmed in several meta-analyses [ 99 , 100 , 101 ]. Regarding ER− BC, up to 31% of them are reported to be AR+ [ 102 ] and although some experimental studies and meta-analyses show that AR positivity is associated with improved outcomes [ 101 , 103 , 104 ], other studies have reported contradictory results [ 7 , 105 , 106 ]. Despite the above, recent evidence have shown that AR pathway activity is increased in all BC subtypes compared with normal breast tissue [ 107 ], making this signaling pathway an interesting target in the study of mammary tumor development and progression.…”
Section: Ar Signaling and Bcmentioning
confidence: 99%
“…Nevertheless, AR significance in BC is still unclear, since AR positivity has been associated with different clinical outcomes in BC patients, according to the ER status. In ER+ BC, AR positivity is considered an independent prognostic factor of a good outcome, but in the subset of ER- BCs, there have been contradictory reports [ 5 , 9 , 10 , 41 ]. Here, the analyses performed in more than seven thousand BC patients showed that AR mRNA levels were significantly higher in women with ER+ tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the significance of its expression is not fully defined, since AR positivity (AR+) has been associated with different clinical outcomes and, contrary biological actions, all of them are apparently dependent on the ER status [ 5 ]. Thus, in ER positive (ER+) tumors, AR positivity is associated with reduced cell proliferation [ 6 ] and favorable clinicopathological features and prognoses [ 7 ], while in ER negative (ER-)/AR+ BC cases, it is generally accepted that AR promotes cell proliferation [ 8 ], although clinical studies have also reported contradictory results [ 9 , 10 ]. In this regard, clinical trials using enobosarm (selective AR modulator—SARM) or antiandrogens (i.e., bicalutamide and enzalutamide), when administered to ER+ BC patients, did not show clinical benefit rates (NCT02463032) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The androgen receptor (AR) can be detected in most breast cancers, but both its expression level and prognostic effect vary. In triple-negative breast cancers (TNBCs), the luminal AR subtype expresses high levels of AR and shows decreased relapse-free survival [7][8][9][10]. In hormone receptor (HR)-positive breast cancers, AR expression is associated with better outcomes [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%